PERTIMBANGAN HAKIM DALAM PUTUSAN SENGKETA DUA MEREK YANG TELAH TERDAFTAR SECARA SAH (Analisis Putusan Nomor 3/Pdt.Sus-HKI/Merek/2020/PN Niaga Mks) - Winata, Natasya Chandra; Yori, A. Kasimirus; Sutanto, Very Werson (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Referring to the dispute of trademark, Decision of Makassar Commerce Public Court Number 3/Pdt.Sus-HKI/Merek/2020.PN Niaga Mks expressly determined that Claimant was The Owner and The First User of Trademark Solaria. Judges extremely ignored the aspect of Solaris Trademark filing validly carried out by Defendant. Judges merely considered normatively to Trademark Acts in turn to ensure the validity of law without remarking justice inside the system of trademark’s protection in Indonesia.